Perception of Law Enforcement Officers on Preventing Road Traffic Injury in Vanuatu: A Qualitative Study - Fanai, Saen; Mohammadnezhad, Masoud; Salusalu, Mosese (Frontiers in Public Health, 2021)
Background: Road traffic injuries (RTIs) cause approximately 1.35 million deaths annually, and is the leading cause of death among people between ages 5 and 29. Law Enforcement Officers (LEOs) deal with RTAs and have contact with RTI victims at a daily basis, they possess an excellent perspective on preventing RTI. This study aimed to explore LEOs perceptions on risk factors and preventive measures of RTI in Vanuatu. Methods: This study employed qualitative methods that used Focus Group Discussions (FGDs) to gather data from LEOs between October 14th to November 30th, 2020. Self-identified Ni-Vanuatu LEOs who have been serving for over 6 months and residing at the study setting wereincluded in this study. Purposive sampling was used to recruit study participants from three municipalities in Vanuatu. A semi-structured open ended questionnaire was designed to guide the FGDs. Data obtained were sorted out using thematic analysis processed with some preconceived themes based on theory, and also allowing the data to determine new themes. Results: Data saturation was reached from conducting 5 FGDs with LEOs who were traffic officers and municipal wardens. Five main themes and sixteen subthemes were generated from the study. The main themes include driving and alcohol, the challenges to effective enforcement, barrers to effective care and support for RTI victims, measures for road traffic control and promoting road traffic safety. The respondents perceived that addressing resources issues and the legislations on road traffic control act and vehicle regulation act will enhance prevention of RTI. Conclusion: This study discovered the risk factors of RTI and the barriers to effectively prevent RTI in Vanuatu. The study also suggested a combination of road traffic control measures that could be implemented to prevent RTI. Future research should look at effective strategies of preventing RTIs in resource deficit settings.